Non-volant mammals from Nucleo Santa Virginia, Serra do Mar State Park, Sao Paulo, Brazil - Rocha-Mendes, Fabiana [UNESP]; Neves, Carolina Lima [UNESP]; Nobre, Rodrigo de Almeida [UNESP]; Marques, Renato Matos [UNESP]; Bianconi, Gledson Vigiano; Galetti, Mauro [UNESP] (Revista Biota Neotropica, 2015)
This study presents data on the composition and species richness of non-flying mammals in the northern part of the Parque Estadual da Serra do Mar, called Nucleo Santa Virginia (NSV - around 17000 hectares of Atlantic Forest), Sao Paulo state, southeastern Brazil. The species list was based on ca. 660 km of line-transects, 25512 hours of cameras traps, 7740 trap. nights for small mammals, and 394 track-station. days, as well as occasional records and registers from local people (period 2002 to 2009). Based on these complementary methods, a total of 58 species were recorded from the 85-104 possible. Eighteen taxa are listed in the Brazilian endangered species list, 29 in the state list. The high species richness of non-volant mammals and the presence of threatened species show the importance of NSV for the conservation of Atlantic Forest mammals.

Este estudo apresenta dados de composic¸a˜o e riqueza de espe´cies de mamı´feros na˜o voadores da porc¸a˜o norte do parque estadual da serra do mar, que corresponde a` regia˜o do nu´cleo santa virgı´nia (nsv – cerca de 17.000 hectares de floresta atlaˆntica), estado de sa˜o paulo, sudeste do brasil. a listagem de espe´cies foi elaborada durante o perı´odo de 2002 a 2009, por meio de ca. 660 km de transecc¸o˜es lineares, 25.512 horas de armadilha fotogra´fica, 394 armadilhas-de-pegada.dia, registros ocasionais e relatos de moradores da regia˜o (entrevistas) para mamı´feros de me´dio e grande porte, e 7.740 armadilhas.noite para pequenos mamı´feros. foram registradas 58 espe´cies de 85-104 de possı´vel ocorreˆncia dada suas potenciais distribuic¸o˜es. dezoito espe´cies fazem parte da lista nacional da fauna ameac¸ada de extinc¸a˜o e 29 da lista estadual. a elevada riqueza de mamı´feros na˜o voadores com a presenc¸a de va´rias espe´cies ameac¸adas, indica a importaˆncia do nsv para conservac¸a˜o da mastofauna regional.
Mamíferos não voadores do Núcleo Santa Virgínia, Parque Estadual da Serra do Mar, São Paulo, Brazil
Keywords: Atlantic forest; Inventory; Mammalia; Sampling methods; Species richness; Floresta Atlântica; Inventário; Mammalia; Métodos de amostragem; Riqueza de espécies